Automatic tracking of labeled red blood cells in microchannels. (12th November 2012) - Pinho, Diana; Lima, Rui; Pereira, Ana I.; Gayubo, Fernando
SUMMARY: The current study proposes an automatic method for the segmentation and tracking of red blood cells flowing through a 100‐ μm glass capillary. The original images were obtained by means of a confocal system and then processed in MATLAB using the Image Processing Toolbox. The measurements obtained with the proposed automatic method were compared with the results determined by a manual tracking method. The comparison was performed by using both linear regressions and Bland–Altman analysis. The results have shown a good agreement between the two methods. Therefore, the proposed automatic method is a powerful way to provide rapid and accurate measurements for in vitro blood experiments in microchannels. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The current study proposes an automatic method for segmentation and tracking of red blood cells flowing through a 100‐ μm glass capillary. The original images were obtained by means of a confocal system and then processed in MATLAB using the Image Processing Toolbox. The measurements obtained with the proposed automatic method were compared with the results determined by a manual tracking method. The comparison was performed by using linear regressions and Bland‐Altman analysis. The results showed a good agreement between the two methods.